Draft Annual Plan, 1993-94 Part-III: Central Sector Plan Schemes Union Territory of Daman and Diu - Planning Commission (Planning Commission, 1993)
This Scheme intends to generate successful models of Development in all the community Development blocks of the Country. Where less than 30% agreeable area is under assumed means of irrigation, it is thus going to be a pace setter for comprehensive development of all our dry land areas and is expected to generate sufficient employments in all the benefits of green revolution to the hither to untouched areas by adopting a farming systems approach on watershed management principles in order to conserve the precious rain water and equally precious, top soil, it is proposed to select two watersheds in Diu district and one in the Daman district during 1992-93 and will be continued for development during 93-94.
Union Territory of Daman and Diu, Department of Planning and Statistics